Computer programming for prediction of soil bulk density effect on trencher design parameters - Dahab, Mohamed Hassan; balal, Moayed Mohamed (International Journal of Agricultural and Biological Engineering, 2012)
A computer program was developed in C++ language to predict the effect of soil bulk density on draft force on bottoms, share thickness, stresses distribution and maximum deflection on standards, bending stresses distribution on side plates, diameter of shear pins, and tensile stress on hitch bar. ?It was found that, as soil bulk density increased, stresses distribution and maximum deflection on standards, bending stresses distribution on side plates, diameter of shear pins, and tensile stress on hitch bar increased. ?The diameter of shear pin should be larger to meet wide range of soil density. Keywords: trencher, computer program, soil, draft force, bulk density, prediction DOI: 10.3965/j.issn.1934-6344.2011.04.042-049 ? Citation: Mohamed Hassan Dahab, Moayed Mohamed balal. ?Computer programming for prediction of soil bulk density effect on trencher design parameters. ?Int J Agric & Biol Eng, 2011; 4(4): 42